The Use of ICT-Based Learning Media in Islamic Religious Education Instruction :An Analysis of the Effectiveness of Islamic Education Teachers at SMP Negeri 1 Idi Rayeuk - Nurdin Nurdin; Sabaruddin Sabaruddin; Lathifah Hanum (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study seeks to investigate the utilization of ICT-based learning media in Islamic Religious Education, evaluate its efficacy in enhancing student learning outcomes, and analyze student attitudes on its implementation at SMP Negeri 1 Idi Rayeuk. A qualitative field research design utilizing a case study methodology was implemented. Data were gathered by observations, interviews, and documentation, and subsequently analyzed descriptively. The results show that IRE teachers at SMP Negeri 1 Idi Rayeuk have used a variety of ICT-based media, such as interactive PowerPoint presentations and Islamic learning films, to make the classroom more interesting, communicative, and participative. Using ICT-based learning tools has been shown to improve both the quality of the learning process and the results for students by making it easier to see abstract ideas through films and animations, which in turn helps students understand and participate more. Additionally, students have very positive views on ICT integration, saying that it makes learning more interesting, fun, and useful in their daily lives. ICT-based media also pique students' attention and curiosity and promote autonomous learning by providing access to digital resources including instructional apps, Islamic websites, and video-sharing platforms.